ANALISIS PERILAKU PELAJAR TERHADAP LINGKUNGAN STUDI KASUS SEKOLAH MENENGAH ATAS DI KABUPATEN BOGOR - Barkatin Barkatin (Graduate School Bogor Agricultural University (SPs IPB), 2016)
One of the causes of environmental problem in Indonesia is human factor, especially human behavior. Students as young generation play very important role on the awareness of environmental condition at school. There are several factors that influence the behavior intention towards environmental behavior of students, including the school environment, community environment, family environment, perception, attitude, subjective norm. Behavior intention affects how attitude of students on the environment. This study aimed to 1) analyze the influence of environmental of school, communities, families, perceptions, attitudes, subjective norm variable to the intention of behavior, 2) analyze the relationship between the intention of behavior to the behavior of students on the environment and 3) formulate strategies to be developed in the schools with regard to the environmental life. The results showed that the intention of behavior is influenced by subjective norms, perceptions, the school environment, attitude, family environment, community environment. SWOT analysis shows that Senior High School in Sub districts Parung,Ciseeng, Gunung Sindurof Bogor Regency is in cell 5 (Growth/Stability).Strategy formulated by the study is introduction of environmental culture school or green school to schools and communities.